KERINDUAN PADA NENEK SEBAGAI SUMBER INSPIRASI PANCIPTAAN KARYA SENI GRAFIS - Ariyadi, Irfan; M, Alexander Nawangseto (Sanggitarupa, 2022)
The deep longing for the love and advice from grandmother, which is ingrained in the person, teaches a lot about the simple way of life as a Javanese. The purpose of creating this work of graphic art is to explain the concept, process, and visual description of a work whose inspiration comes from longing for one's grandmother. The technique used is the printing technique (Intaglio). The creation of this Final Project graphic artwork provides more insight regarding the tools, materials, techniques to work on a work. The result obtained from the creation of the work is a work of graphic art inspired by a sense of longing for grandmothers. In addition, empirical experience in creating works of art is also a deepening of the concept of longing for grandmothers.